Prevalence of post traumatic stress symptoms after childbirth among postnatal mothers in Dhulikhel. - Maharjan, Indira (2010)
ABSTRACT: Title: Prevalence of Post traumatic Stress Symptoms after Childbirth among postnatal mothers in Dhulikhel Background: The increased acceptance of prevalence of trauma in human experience as well as its psychological consequences had led to revisions of diagnostic criteria for post traumatic stress disorder. Recent research shows that a proportion of women experience significant symptoms of post traumatic stress disorder after childbirth. Purpose: To find out the prevalence of post traumatic stress symptoms after childbirth. Method: This simple descriptive cross sectional study assessed 100 postnatal women during 1 month to 6 months after childbirth in Dhulikhel. The prevalence of post traumatic stress disorder was assessed by using questionnaire by interview. Results: 6 percent of women fulfilled criteria for this disorder and 80 percent of them were partially symptomatic.22 percent developed symptoms occasionally and 2 percent developed no symptoms. This study was unable to establish association between post traumatic stress symptoms and socio-demographic and obstetric characteristics. Conclusion: A proportion of women report all three aspects of post traumatic stress symptoms following childbirth with many more reporting some symptoms. It is important to increase awareness about the disorder. Intervention is possible at several levels, but further research is needed to guide this intervention. Keywords: prevalence, Post traumatic stress symptoms, childbirth